Coming into Life with Education: Definitions, Difficulty and Meaningfulness in Conceptual Aesthetics - Gibbs, Alexis (Philosophical Inquiry in Education, 2021)
What do we mean by the word “education”? How do others know what we mean when the term is under constant revision? Do we even need definitive answers in order to speak meaningfully of it? This paper attempts to explore the potential for education’s meaningfulness via attention to its ordinary usages. In order to justify the need to be attentive to the specific instance of use, I will explore the closing down of conceptual meaning represented by acts of definition. In taking a closer look at what definitions of education try to do when they are articulated, I will follow a line of argument from Cora Diamond that the definition and explanation of a term can constitute a deflection from the difficult “reality” of educational discourse, a reality that poses its own problems in turn, but also should not be ignored. Attending to “education” as a word that appears with particular meanings in particular instances reveals the richness of the various forms it can assume. I describe this as a conceptual aesthetics of education.